An exploratory study of the motivation and retention of adult high-functioning volunteers in community-based non-profit organizations - Diamond, Sarah D. (Kansas State University, 2017)
Non-profit organizations come in many shapes and sizes and in some cases, encompass a significant portion of community organizations. Since these agencies are largely sustained by the work of volunteers, it is a worthy subject to examine. The diversity and complexity of non-profits available among communities presents a need for volunteers’ to be skilled, trained, and experienced in an array of arenas. Non-profit organizations depend on volunteers and allow these entities to reach a larger population than exclusively with the limited staff members available (Fisher & Cole, 1993). This notion suggested the topic of motivation and retention of volunteers among community non-profits for the focus of this study to help organizations effectively deliver their mission. More specifically, this investigation centered on people who are considered high-functioning by the administrators with whom they work through the process of interviews. Non-profit organizations located in Denver, Colorado were selected to participate. The administrators of the chosen agencies were contacted and asked to identify volunteers in their program they classify as high-functioning. Once this list was identified, these individuals were contacted and asked to participate in an interview. This study focused on high-functioning volunteers for data collection because it was anticipated their characteristics and viewpoints will aid in the understanding of motivation and retention factors for anyone working with and supervising volunteers in the 21st century. The findings from the study provide a diverse assessment of the topic of volunteer motivation and retention. The data collected suggests that adult volunteers have varying needs and the importance for volunteer administrators to take these differences into consideration in their management and programming efforts.
Keywords: Community-based non-profit organizations; Volunteers; High-functioning volunteers; Motivation and retention; Volunteer administratorsNon-profit organizations